Nowcasting poverty and inequality in the context of economic growth and Covid-19 pandemic in Lithuania - Gabnytė, Vitalija; Čižauskaitė, Aušra; Navickė, Jekaterina (Lithuanian Journal of Statistics, 2021)
The purpose of this article is to present a methodology and results for nowcasting poverty and inequality indicators during economic growth and the Covid-19 pandemic in Lithuania. Nowcasting combines the techniques of tax-benefit microsimulation and calibration of the survey weights. For the microsimulation, the tax-benefit microsimulation model EUROMOD is used together with its additional components for Lithuania, which were developed by the Ministry of Social Security and Labour of the Republic of Lithuania. Three economic forecasts, developed by the Bank of Lithuania for 2020, are used: the rapid V-shaped recovery scenario, intermediate U-shaped recovery scenario and a slow extended U-shaped recovery scenario. The results show Lithuania’s favourable tendencies in reducing poverty and inequality in the general population and by age groups in the context of rapid economic growth and improving the improved labour-market situation in 2018–2019. The results of 2020 suggest that relative at-risk-of-poverty rates and inequality in the country are likely to decline. The foreseen decrease in the at-risk-of-poverty rate is primarily due to reducing poverty risk among older people and children. The most vulnerable age groups include youth (18–24 years) and the elder working-age population (50–64 years). Poverty rates for these groups are likely to increase in 2020. However, it should be noted that the at-risk-of-poverty rates had also declined in Lithuania during the first years of the previous economic crisis. Decomposition of demographic/employment changes and policy effects for 2019–2020 show that due to demographic and employment changes, poverty and inequality is likely to increase in Lithuania in 2020. The impact of the policy effect is progressive, more favourable to the less well-off, leading to a reduction in poverty. Progressiveness is due to the fact that during the quarantine period, flat benefits were provided to a large part of the society: children, pensioners, job-seekers, self-employed.